Angiotensin‐converting enzyme inhibition, antioxidant activity and cytotoxicity of bioactive peptides from fermented bovine colostrum. (20th October 2019) - Gaspar‐Pintiliescu, Alexandra; Oancea, Anca; Cotarlet, Mihaela; Vasile, Aida Mihaela; Bahrim, Gabriela Elena; Shaposhnikov, Sergey; Craciunescu, Oana; Oprita, Elena Iulia
Abstract : Fermented bovine colostrum rich in bioactive peptides was obtained using Candida lipolytica strains in co‐culture with kefir grains. During fermentation, the pH and total titratable acidity of the product were daily measured. The hydrolysis degree and the electrophoretic pattern of water‐soluble extracts (WSE) of fermented colostrum were analysed. Fractions enriched in peptides with a molecular weight lower than 10 kDa were separated by ultracentrifugation. They showed better modulation of angiotensin‐converting enzyme (ACE) inhibition and cell proliferation, but lower radical scavenging capacity, compared to corresponding WSE.